Sectoral risk and return: Implications on commercial banks' credit expansion in Kenya - Ferdinand Othieno; Caroline Kariuki (Kenya Bankers Association (KBA), 2017)
The paper examines the effect of sectoral risk on bank returns that accrue from the extension of credit to the different sectors of the economy in Kenya. Based on Dynamic Panel Data regressions of quarterly sectoral data spanning from 2011Q1 to 2015Q4 the paper reports three key findings: (1) There is no strong evidence of risk-based pricing since the risk-return relationship although positive, it is statistically insignificant. (2) There is no evidence of a U-shaped or non-linear relationship between risk and return regardless of the measure of risk, (3) Sectoral credit expansion is significantly impacted by returns and risk. Whereas the pricing effect is not as sensitive to the risk profile of the respective sectors, credit availed to the sectors is highly risk sensitive regardless of the measure of risk; effectively higher risk ratings seem to drive credit availability as opposed to pricing of the extended loans. The results question the risk-pricing nexus in the Kenyan market, if the risk is at least measured at the sectoral level.
Keywords: 330; Commercial Banks; Credit expansion; Dynamic Panel Data Analysis